Spousal Support Practices Among Women Attending Antenatal Clinic at Adeoyo Maternity Teaching Hospital, Ibadan, Oyo State, Nigeria (African Journal of Biomedical Research, 2023)
Spousal role in maternal health is frequently ignored by health programs in emerging countries. This study examined the level of spousal support for good pregnancy outcome among women attending antenatal clinic at Adeoyo Maternity Teaching Hospital, Ibadan, Oyo State, Nigeria. This study was conducted among 398 pregnant women attending antenatal clinic at the study location. Semi-structured questionnaire was used for data collection. The data were analyzed using descriptive statistics. The mean age of respondents was 30±5.6years.  55.5% were Muslims while 44.5% were Christians. Less than half (47.5%) of the respondents had tertiary education. 50.8%  of the respondents’ stated that their spouse encouraged them to register at the hospital; and almost all (97%) of the respondents indicated that their spouse supported their antenatal care attendance. Moreover, 63.1% of the respondents stated that their husbands did not accompany them to antenatal classes which was as a result of their work. More than half (52.8%) of the respondents indicated that their husbands accompanied them for ultrasound scan and 91.0% of the respondents stated that their husbands’ saved money towards their delivery in case of emergency and referral. Overall results displayed that 88% of respondents had good spousal support practices while 12% had fair spousal support practices. The findings of the study revealed that level of spousal support among pregnant women in the study location was high